Assistance for Pregnant Women Reducing Chronic Energy Deficit Cases - Kaparang, Mercy Joice; Noya, Fransisca; Tempali, Sri Restu (Poltekkes Kemenkes Palu, 2025)
Introduction: Chronic energy deficiency (CED) in pregnant women is a significant public health concern in Indonesia, with a prevalence of 17.3% in 2018. This study aimed to analyze the implementation of stunting prevention in CED pregnant women by providing exclusive breastfeeding until the baby is 6 months old in Central Sulawesi Province. Methods: A quantitative analytical approach with a group pre-test–post-test design was employed. The study was conducted at the Kampung Baru Health Center, Luwuk Banggai Regency, and the Lambunu 2 Health Center, Parigi Moutong Regency, between May and August 2023. The sample consisted of 38 pregnant women with CED, selected using purposive sampling. Data were collected through questionnaires on maternal knowledge about nutrition for pregnant women and exclusive breastfeeding. The intervention included providing health education on nutrition and a balanced menu for pregnant women, exclusive breastfeeding, and recording the consumption of supplementary feeding (PMT) biscuits. Results: The results showed a significant increase in mothers' knowledge about nutrition for pregnant women and exclusive breastfeeding after the intervention (p<0.05). Additionally, there was a significant reduction in the incidence of CED after the intervention (p=0.000). Conclusions: The study concludes that providing assistance to pregnant women through health education and PMT biscuits can effectively reduce the incidence of CED and improve maternal knowledge about nutrition and exclusive breastfeeding. These findings highlight the importance of implementing comprehensive interventions to prevent stunting and improve maternal and child health outcomes in Indonesia.